The Role of Technological Media in the Character Building Education Process for Generation Z: A Literature Review - Shinta Shinta; Muh. Azhar; Partino Partino; Fitriah M. Suud (Postgraduate, University of Mataram, 2024)
This research aims to determine various technology-based media used in the world of education to shape character for Generation Z Research design and method should be clearly defined. The method in this research is a literature review of various research studies published in Scopus-indexed journals. This is the basis for researchers to choose general keywords, namely